2017
DOI: 10.1038/s41598-017-01411-1
|View full text |Cite|
|
Sign up to set email alerts
|

Immune-checkpoint protein VISTA critically regulates the IL-23/IL-17 inflammatory axis

Abstract: V-domain Immunoglobulin Suppressor of T cell Activation (VISTA) is an inhibitory immune-checkpoint molecule that suppresses CD4+ and CD8+ T cell activation when expressed on antigen-presenting cells. Vsir−/− mice developed loss of peripheral tolerance and multi-organ chronic inflammatory phenotypes. Vsir−/− CD4+ and CD8+ T cells were hyper-responsive towards self- and foreign antigens. Whether or not VISTA regulates innate immunity is unknown. Using a murine model of psoriasis induced by TLR7 agonist imiquimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 52 publications
(73 reference statements)
2
65
0
Order By: Relevance
“…While this can function in suppressing T cell activation in an autologous manner, a study using imiquimod-induced murine psoriasis demonstrated that VISTA inhibits the activation of DCs and the production of IL-23 following TLR 7 activation. 110 The same study also demonstrated that VISTA negatively regulates the activation of IL-17producting γδ T cells and Th17 cells. 110 Therefore, it is conceivable that at least some aspects of VISTA blockade in boosting antitumor immunity involve releasing the brakes on innate immunity.…”
Section: Inhibition Of Checkpoints At the Interface Of Innate And Adamentioning
confidence: 82%
See 1 more Smart Citation
“…While this can function in suppressing T cell activation in an autologous manner, a study using imiquimod-induced murine psoriasis demonstrated that VISTA inhibits the activation of DCs and the production of IL-23 following TLR 7 activation. 110 The same study also demonstrated that VISTA negatively regulates the activation of IL-17producting γδ T cells and Th17 cells. 110 Therefore, it is conceivable that at least some aspects of VISTA blockade in boosting antitumor immunity involve releasing the brakes on innate immunity.…”
Section: Inhibition Of Checkpoints At the Interface Of Innate And Adamentioning
confidence: 82%
“…110 The same study also demonstrated that VISTA negatively regulates the activation of IL-17producting γδ T cells and Th17 cells. 110 Therefore, it is conceivable that at least some aspects of VISTA blockade in boosting antitumor immunity involve releasing the brakes on innate immunity.…”
Section: Inhibition Of Checkpoints At the Interface Of Innate And Adamentioning
confidence: 82%
“…Research is currently ongoing to characterize the cell-signaling mechanisms triggered by VISTA.COMP in both mouse and human T cells. Nonetheless, our data, combined with the observation of exacerbated autoimmune diseases upon genetic deletion of VISTA (15)(16)(17)(18), suggest a potential utility of targeting the VISTA-mediated immunosuppression pathway using a high-avidity VISTA-IgV containing scaffold to clinically suppress undesired immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was shown that VISTA-deficient mice exhibited worsened disease in a model of imiquimod-induced psoriasis, where enhanced TLR7 signaling in DCs led to augmented IL-23 production and increased expression of IL-17A in T cells (17). The VISTA -/-mice bred on a wild-type C57BL/6 background display a mild proinflammatory phenotype, exemplified by an increase in DCs and a rise in T cell activation markers, but were not reported to develop inflammatory disorders (16).…”
Section: Introductionmentioning
confidence: 99%
“…Combination VISTA/PD-L1 blockade produced greater antitumor effects than either agent alone, suggesting that VISTA and PD-1/PD-L1 signaling have overlapping but nonredundant inhibitory effects on CD8 T cells [178]. The effects of VISTA blockade appears to be mediated by IL-23/IL-17 axis, although how IL-17 regulates TA-specific adaptive immunity remains to be clarified [179].…”
Section: Lag-3: Preclinical and Clinical Datamentioning
confidence: 99%